Nasal cylindrical cell papilloma - Subha, Sethu Thakachy; Prepageran, Narayanan (Malaysian Medical Association, 2005)
Inverted papilloma is the most common benign tumor of nose and paranasal sinuses arising from lateral nasal wall and middle meatus. Histologically these tumors are composed of epithelial nests that are inverted, exophytic and cylindrical. Here we describe a clinical case of nasal cylindrical cell papilloma, which was treated by endoscopic excision.